Opioid based versus opioid free general anaesthesia in laparoscopic surgeries: A Randomised double blinded clinical study - Meghana, Puppala; Kanase, Naseema V; Dhulkhed, Vithal; D, Naveen (Journal of Neonatal Surgery, 2025)
Background: To mitigate the adverse effects associated with opioid use, opioid-free multimodal analgesic approaches are being investigated. Opioid-free anaesthesia may improve postoperative recovery by minimising opioid-related complications AIM:To compare the effects and postoperative outcome for participants receiving opioid-based versus opioid-free general anaesthesia in laparoscopic surgeries. Methodology: This randomised double-blinded clinical trial included 82 patients scheduled for laparoscopic surgery, allocated into two equal groups (n = 41 each). Group A: (opioid-free) received a combination of Dexmedetomidine (0.3 mcg/kg), lignocaine (1 mg/kg), ketamine (0.2 mg/kg). Group B :(opioid-based) received fentanyl 10mcg/ml during induction. Depth of anaesthesia and hemodynamic parameters were monitored intra and post operatively. Postoperative pain was assessed using VAS scores and the time to first rescue analgesia along with incidence of postoperative side effects was recorded. Results: Group A had significantly lower MAC of Sevoflurane (0.92 ± 0.12) compared to Group B (1.34 ± 0.15) (p < 0.001). Postoperative VAS scores at all time points (1h to 12h) were significantly lower in Group A. Time to first analgesic request was delayed in Group A, with fewer rescue analgesics required.Opioid-free anaesthesia group also had fewer side effects like nausea and vomiting. Conclusion: Opioid-free anaesthesia using a multimodal regimen is a safe and effective alternative to opioid-based anaesthesia in laparoscopic surgeries. It offers comparable intra operative stability and postoperative pain control, with fewer postoperative side effects.